Trends in gestational age at birth in the city of São Paulo, Brazil between 2012 and 2019 - Margarida Maria Tenório de Azevedo Lira; Marina de Freitas; Eliana de Aquino Bonilha; Célia Maria Castex Aly; Patrícia Carla dos Santos; Denise Yoshie Niy; Carmen Simone Grilo Diniz (PLoS ONE, 2025)
Studies have shown that excessive obstetric interventions such as induced labor and caesarean sections have contributed to the shortening of the length of gestation, leading to a left shift in gestational age (GA) at birth. The aim of this study was to analyze trends in GA and the contribution of associated factors to changes in São Paulo city, Brazil during the period 2012–2019. We conducted an observational time-series study of births in São Paulo using data from Brazil’s national live births information system (SINASC). We calculated the annual percent change (APC) of births by GA between 2012 and 2019 and between the first and second four-year periods of the time series by applying log transformation to the percentages, followed by Prais-Winsten regression. A total of 1,525,759 live births were analyzed. From 2015, there was an increase in the proportion of live births between 39 and 40 weeks from 2015 and a fall in the proportion of early term (37–38 weeks) and preterm (< 37 weeks) births throughout the study period. The APC of births at 39 and 40 weeks was 7.9% and 5.7%, respectively, while the proportion of births at other gestational ages showed a statistically significant reduction over the study period. These reductions were more pronounced in the first four-year period (2012–2015). The same trend was observed when the data were analyzed by type of delivery, type of service (public or private), maternal age, and maternal education level. The findings show that there was a right shift in the GA curve during the study period and a reduction in the proportion of preterm and early term births. These changes were more pronounced in births that occurred in private hospitals. These changes reflect public policies implemented to reduce obstetric interventions such as induced labor and caesarean section before labor, especially before 39 weeks of gestation.